Adenosine triphosphate citrate lyase mediates hypocitraturia in rats. - J Z Melnick; P A Srere; N A Elshourbagy; O W Moe; P A Preisig; R J Alpern (The Journal of Clinical Investigation, 1996)
Chronic metabolic acidosis increases proximal tubular citrate uptake and metabolism. The present study addressed the effect of chronic metabolic acidosis on a cytosolic enzyme of citrate metabolism, ATP citrate lyase. Chronic metabolic acidosis caused hypocitraturia in rats and increased renal cortical ATP citrate lyase activity by 67% after 7 d. Renal cortical ATP citrate lyase protein abundance increased by 29% after 3 d and by 141% after 7 d of acid diet. No significant change in mRNA abundance could be detected. Hypokalemia, which causes only intracellular acidosis, caused hypocitraturia and increased renal cortical ATP citrate lyase activity by 28%. Conversely, the hypercitraturia of chronic alkali feeding was associated with no change in ATP citrate lyase activity. Inhibition of ATP citrate lyase with the competitive inhibitor, 4S-hydroxycitrate, significantly abated hypocitraturia and increased urinary citrate excretion fourfold in chronic metabolic acidosis and threefold in K+-depletion. In summary, the hypocitraturia of chronic metabolic acidosis is associated with an increase in ATP citrate lyase activity and protein abundance, and is partly reversed by inhibition of this enzyme. These results suggest an important role for ATP citrate lyase in proximal tubular citrate metabolism.